Rising incidence of malignancy in thyroid nodule: a clinico radio pathological evaluation - Kapoor, Abha A.; Anand, Akash M.; Nimkar, Nimisha U.; Soni, Hiren D.; Panchal, Rutul B.; Kapoor, Abhay A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Thyroid nodules are a common endocrine problem with varied aetiology and presentation. Benign nodules also need to be evaluated in detail for possibility of malignancy in today’s era of rising incidence of malignancy. This study aims to comparatively analyse and verify the incidence of malignancy reported in tertiary care hospital with incidence of malignancy published in standard journals and research. The study also endeavours to clinically examine solitary thyroid nodules in patients admitted to the tertiary care centre. Methods: A retrospective study was carried out from 2019 to 2022, in the Department of ENT, in a Tertiary Care Hospital. Thirty patients, with solitary thyroid nodule, were clinically examined and investigated using ultrasonography and Fine Needle Aspiration Cytology, before undergoing hemi/total thyroidectomy. The histopathological reports and pre-operative investigations were analysed by standard statistical methods. Results: Clinically detected solitary thyroid nodule turned out to be malignant in 30% of studied cases with preponderance of papillary carcinoma. This figure is significantly higher than most of the previous data published in standard journals. A rare case of cystic presentation of anaplastic thyroid carcinoma was also studied. Conclusions: It is concluded from the present study that incidence of malignancy has shown sharp rise- from the published average of 19-21 percent to 30 percent in the present case. The study also infers that there is female preponderance in thyroid swellings. The mean age of solitary thyroid nodule is 35 years i.e., between 30 to 40 years.